Efektivitas Program Pemberdayaan Residivis Untuk Meningkatkan Konsep Diri - Rahatmidewi, Mulyasari, Dr. Lisnawati Ruhaena, M.Si., Psikolog, Wisnu Sri Hertinjung, S.Psi, M.Psi, Psi (2017)
The purpose of this is study was to determine the ffectiveness of recidivists empowerment programs to increase positive self-concept. This study was an experimental study with empowerment program intervention. The subjects were recidivists in class 1 Surakarta State Prison, which 16 person had a self-concept on a middle category. Method of collecting data was used self-concept scale Tennessee Self Concept Scale (TSCS). This research method is a two-group pretest-posttest design, with the determination of members of both the control and the experimental group using random assignment. The analysis showed that, recidivist empowerment program effective in improving positive self-concept. In addition, there are significant differences between self-concept on experimental group and the control group, so it can be concluded that the recidivism empowerment program can increase positive self-concept. The increased of positive self-concept on recidivist could seen by realize their mistake, face the condition, began openly with others, looked calmer, looked confident, optimistic about their future, had insight to apologize their parents, will to meet their friends, had a job to do, feel better and start to plan for the future after his release, and expect the continuity about those program. The most dominant method favored by recidivists was discussion group in the form of counseling and relaxation methods, as in the rest of the period of custody the recidivist needs others to share, support and attention to motivate them. Keywords: ffectiveness, recidivist Empowerment Program, Self-Concept, Experiment